Not without you - Evans, Harriet, 1974- (Gallery Books, 2014)
"From international favorite and bestseller Harriet Evans, an absorbing and intriguing new novel about a famous modern-day actress whose fate becomes entwined with that of a glamourous movie star from the 1950s who vanished many years earlier"--